Lecturers’ oral corrective feedback in speaking class: Students’ perceptions - Asnawi Muslem; T Zulfikar; Inas Astila; Bustami Usman; Arifin Syamaun (Proceedings of AICS - Social Sciences, 2017)
Many researchers conducted the research on the implementation of methods of teaching and learning English in the classroom setting. However, not many researchers focused on the aspects of feedback from the lecturers in improving students’ speaking performance. Therefore, this paper aimed at investigation students’ perception towards lecturers’ oral corrective feedback in speaking classes. This survey involved 100 students of English Language Education Department, Ar-Raniry State Islamic University (UIN Ar-Raniry) Banda Aceh from 254 students. The participants of the survey were selected using simple random sampling technique to represent all off the population. A modified questionnaire from Calsiyao (2015, p. 397) and Elsaghayer (2014, p. 77) was used to collect the data. The percentage was employed to analyze the data collected from questionnaire. The results showed that the students perceived lecturers’ oral corrective feedback as an important part of language learning. Lecturers’ oral corrective feedback was very helpful in improving the students’ speaking ability. It can be concluded that the oral corrective feedback gave positive size towards students’ speaking performance. Therefore, this research is significant to be conducted to highlight the students’ perception towards oral corrective feedback from their lecturers during the teaching and learning speaking in the class. Both lecturers and students would benefit from this research so that they can realize that how important to give and accept oral corrective feedback.